Critical thinking development in a Quality Matters-based online learning: student insights from a South African higher education context - Gold, Nusirat Ojuolape; Coovadia, Husain; Mahmood, Tasneem (Frontiers in Education, 2025)
IntroductionThe transition in learning mode from traditional systems to online modes is attracting continuous attention globally. For quality assurance, universities are increasingly adopting online teaching design structured using standards like the “Quality Matters” (QM) rubrics, which are aimed at ensuring continuity and greater accessibility to education. This study investigates students' perception of the impact of online learning designed using QM on critical thinking (CT) development among accounting students at a South African university. Despite the widespread adoption of the QM for online learning platform design, research investigating its specific influence on CT is scarce. Grounded in the constructivist learning theory and the technology acceptance model, the research investigates four key objectives: the impact of QM-aligned online courses on CT, the effectiveness of structured course design in enhancing CT, the role of technology and institutional support in bridging the digital divide, and strategies for optimizing online learning components to foster CT.MethodUsing data gathered through a structured questionnaire, the study employed principal component analysis (PCA) to identify six thematic components that significantly contribute to fostering CT development.ResultNotably, the significance of engaging resources, course clarity, learner interaction, feedback, and technology accessibility. The findings underscore the importance of well-structured, accessible, and engaging online platforms. They also highlight that technology and institutional support are pivotal to fostering CT development.DiscussionAlthough limited to a single institution and relying on self-reported perceptions, the study offers valuable insights into optimizing online course design. Therefore, this study provides recommendations for educators, institutions, and course developers and offers a foundation for future research across diverse educational contexts.